Small molecule conjugation reduces macrophage uptake and increases in vivo blood circulation of polystyrene nanoparticles - Yenurkar D.; Ruocco M.; Pragya; Liang L.; Mukherjee S. (My University, 2025)
Nanomedicine often failed clinically to show therapeutic efficacy due to reduced particle circulation and enhanced capture by the reticuloendothelial system, including the liver. Developing novel immunomodulatory surface coating can prevent macrophage capture and increase the particle circulation of the nanomedicine, resulting in higher therapeutic efficiency. Herein, we demonstrate the development of immunomodulatory small molecule (RZA15) with triazole functionality using copper-catalyzed click chemistry to conjugate onto spherical polystyrene nanoparticles (NPs) using amide coupling reactions, achieving higher blood circulation and lesser macrophage uptake of the nanoconjugates (NCs). In this work, we evaluated the effectiveness of RZA15 coating for the enhanced circulation of polystyrene NPs of 100 nm size, which is commonly utilized for various drug delivery applications, and compared with poly(ethylene)glycol coatings. Several polystyrene NC formulations were analyzed in vitro in normal and macrophage cells for cell viability and cellular uptake studies. In vitro studies demonstrated lesser macrophage uptake of the NCs following RZA15 coating. Finally, in vivo, blood-circulation, pharmacokinetics, and biodistribution studies were performed in the C57BL/6J mouse model that endorsed the substantial role of RZA15 in reducing liver and spleen capture and results in extended circulation in blood. Coating immunomodulatory small molecules to nanoparticles can severely enhance the potential therapeutic effects of nanomedicine at lower doses in near future. © 2024 IOP Publishing Ltd